Satisfaction, trust, and risk perception as antecedents of customer loyalty - Astriani, Iis (Journal of Management and Business Insight, 2023)
Purpose-Customer loyalty is an important aspect that must be owned and maintained by every business actor. Maintaining customer loyalty increases opportunities for businesses to survive in business competition. Many internal or external factors can affect customer loyalty. This study aimed to determine how satisfaction, trust, and risk perception affect customer loyalty. Design/Methodology/Approach-Smart PLS 4.0 is a statistical tool used to process research data. This study analyzes the effect of satisfaction, trust, and risk perception on customer loyalty to Tokopedia customer objects. Research data were obtained by distributing questionnaires and collecting data from up to 96 respondents. Findings-Two of the three hypotheses were rejected or unsupported. Satisfaction and risk perception had no effect on consumer loyalty, while trust had a positive effect on consumer loyalty. Research limitations/implications-The findings of this research are expected to be a reference and learning, especially for business actors in Tokopedia, who are expected to be able to understand that to grow or maintain consumer loyalty, there are many things that must be considered. This study shows that satisfaction, trust, and risk perception are factors that can affect customer loyalty. Originality/value-There is still very little research on consumer behavior, especially customer loyalty, using the Tokopedia e-commerce service. In this study, factors that influence consumer behavior, especially Tokopedia consumer loyalty.